2010
DOI: 10.1051/0004-6361/200913712
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent outflows at the edge of an active region – a possible source of the solar wind?

Abstract: Context. It has already been established that the solar wind may originate at the edges of active regions (ARs), but the key questions of how frequently these outflows occur, and at which height the nascent solar wind originates have not yet been addressed. Aims. We study the occurrence rate of these intermittent outflows, the related plasma activities beneath in the low solar atmosphere, and the interplanetary counterparts of the nascent solar wind outflow. Methods. We use the observations from XRT/Hinode and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 49 publications
6
43
1
Order By: Relevance
“…It should be noted that the findings presented here are quite different from the studies of Doschek et al (2008) or He et al (2010) who also find evidence of a wind outflow in the periphery of an active region. However, they only investigate single Gaussian fits.…”
Section: Solar Wind Outflow From Filamentary Funnels?contrasting
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the findings presented here are quite different from the studies of Doschek et al (2008) or He et al (2010) who also find evidence of a wind outflow in the periphery of an active region. However, they only investigate single Gaussian fits.…”
Section: Solar Wind Outflow From Filamentary Funnels?contrasting
confidence: 99%
“…Thus one can speculate that the Doschek et al (2008) and the He et al (2010) data actually show the same effect of a high-velocity component, which will have to be checked by re-examining their data.…”
Section: Solar Wind Outflow From Filamentary Funnels?mentioning
confidence: 98%
“…These chromospheric small-scale ejections could be masked by the low spatial resolution of EIS and spatially appear as unresolved large-scale flows. As a result of the frequency of occurrence of these kinds of jets and their ubiquitousness, the chromospheric origin of the AR upflows has been proposed (McIntosh & De Pontieu 2009;He et al 2010;Nishizuka & Hara 2011). The IBIS data provide a unique opportunity for exploring this idea.…”
Section: Ibismentioning
confidence: 99%
“…McIntosh & De Pontieu (2009) suggested that blueward asymmetries observed in the Si vii (log T max = 5.8 K), Si x (log T max = 6.1 K) and Fe xiv (log T max = 6.3 K) lines near ARs may be a result of spicular activity in the chromosphere. He et al (2010) used Hinode Solar Optical Telescope (SOT) data in Ca ii H to study the plage area underlying coronal outflows. The authors reported three jets that occurred in a small area over a period of one hour and "inferred that the intermittent coronal outflow might be caused by the chromospheric jets".…”
Section: Introductionmentioning
confidence: 99%
“…Although several indirect observations (McIntosh & De Pontieu 2009;He et al 2010;Nishizuka & Hara 2011) have indicated a correlation between jets in the chromosphere and coronal upflows, in Paper I it has been shown through chromospheric spectroscopic imaging that the upflows persists despite the absence of chromospheric jets, indicating that the driving should be located higher in the atmosphere.…”
Section: Introductionmentioning
confidence: 98%